Prevalence of Mycoplasma genitalium by anatomical site in men who have sex with men: a systematic review and meta-analysis. Issue 8 (27th April 2020) - Latimer, Rosie L; Shilling, Hannah S; Vodstrcil, Lenka A; Machalek, Dorothy A; Fairley, Christopher K; Chow, Eric P F; Read, Tim RH; Bradshaw, Catriona S
Abstract : Objective: To systematically review and appraise published data, to determine the prevalence of Mycoplasma genitalium (MG) in men who have sex with men (MSM) tested at each anatomical site, that is, at the urethra, rectum and/or pharynx. Design: Systematic review and meta-analysis. Data sources: Ovid Medline, PubMed, Embase were searched for articles from 1st January 1981 (the year MG was first identified) to 1st June 2018. Review methods: Studies were eligible for inclusion if they reported MG prevalence in MSM tested at the urethra, rectum and/or pharynx, in at least 50 MSM, using nucleic acid amplification testing. Data were extracted by anatomical site, symptom and HIV status. Summary estimates (95% CIs) were calculated using random-effects meta-analysis. Subgroup analyses were performed to assess heterogeneity between studies. Results: Forty-six studies met inclusion criteria, with 34 reporting estimates of MG prevalence at the urethra (13 753 samples), 25 at the rectum (8629 samples) and 7 at the pharynx (1871 samples). MG prevalence was 5.0% (95% CI 3.5 to 6.8; I 2 =94.0) at the urethra; 6.2% (95% CI 4.6 to 8.1; I 2 =88.1) at the rectum and 1.0% (95% CI 0.0 to 5.1; I 2 =96.0) at the pharynx. The prevalence of MG was significantly higher at urethral and rectal sites in symptomatic versus asymptomatic MSM (7.1% vs 2.2%, p<0.001; and 16.1% vs 7.5%, p=0.039, respectively). MG prevalence at the urethra was significantly higher in HIV-positive compared with HIV-negative MSM (7.0% vs 3.4%, p=0.006). Conclusion: MG was common in MSM, particularly at urethral and rectal sites (5% to 6%). MG was more commonly detected in symptomatic men at both sites, and more common in HIV-positive men at the urethra. MG was uncommonly detected in the pharynx. Site-specific estimates are similar to those for chlamydia and will be helpful in informing testing practices in MSM. PROSPERO registration number: CRD42017058326.